HEGEMONI DALAM KUMPULAN CERPEN TEH DAN PENGKHIANAT KARYA IKSAKA BANU - Budiman, Putra Ariq; Suhardi , Imam; Nani Hari Yanti, Sri (University of Brawijaya, 2024)
This research discusses the aspect of hegemony in the short story collection